An audit of MTP in women with high-risk pregnancy - Deepali Srivastava (Manipal College of Medical Sciences, Pokhara, 2021)
Background: The women who have been pregnant more than four times are fewer than 18or over 35-years-old, or have at least one medical issue before or during pregnancy, the pregnancy is considered high-risk. Increased maternal and foetal mortality and morbidity are linked to these risk factors. MTP in itself is a blind and risky procedure and performing it in High Risk Pregnancy (HRP) is a challenge for obstetrics and gynecology personnel. When performed with all pre, intra and post-op precautions, results are good and patient-friendly.